Real-world first-line treatment and overall survival in non-small cell lung cancer without known EGFR mutations or ALK rearrangements in US community oncology setting. - Amy P Abernethy; Ashwini Arunachalam; Thomas Burke; Caroline McKay; Xiting Cao; Rachael Sorg; David P Carbone (PLoS ONE)
Purpose To establish a baseline for care and overall survival (OS) based upon contemporary first-line treatments prescribed in the era before the introduction of immune checkpoint inhibitors, for people with metastatic non-small cell lung cancer (NSCLC) without common actionable mutations. Methods Using a nationally representative electronic health record data from the Flatiron dataset which included 162 practices from different regions in US, we identified patients (≥18 years old) newly diagnosed with stage IV NSCLC initiating first-line anticancer therapy (November 2012- January 2015, with follow-up through July 2015). Patients with documented epidermal growth factor receptor (EGFR) or anaplastic lymphoma kinase (ALK) translocation were excluded. Anti-cancer drug therapy and overall survival were described overall, and by histology. Results A total of 2,014 patients with stage IV NSCLC without known EGFR or ALK genomic tumor aberrations initiated systemic anticancer therapy, 22% with squamous and 78% with nonsquamous histology. Their mean (SD) age was 67 (10) years, 55% were male, and 87% had a smoking history. In nonsquamous NSCLC, carboplatin plus pemetrexed either without (25.7%) or with bevacizumab (16%) were the most common regimens; 26.6% of nonsquamous patients receiving induction therapy also received continuation maintenance therapy. In squamous NSCLC, carboplatin plus paclitaxel (37.6%) or nab-paclitaxel (21.1%) were the most commonly used regimens. Overall median OS was 9.7 months (95% CI: 9.1, 10.3), 8.5 months (95% CI: 7.4, 10.0) for squamous, and 10.0 months (95% CI: 9.4, 10.8) for nonsquamous NSCLC. Conclusion The results provide context for evaluating the effect of shifting treatment patterns of NSCLC treatments on patient outcomes, and for community oncology benchmarking initiatives.